La interculturalidad en el desempeño docente en Educación General Básica de la UEIB “Angel Erminio Silva Olivo” periodo lectivo 2020-2021. - Cando Bravo, Luis Milton (2022)
Interculturality is an essential component in the teaching-learning processes of educational institutions, and in rural communities with indigenous populations it is more significant, because it promotes and improves the appreciation of traditions and customs that are part of their identity and cultural relevance. In Alausí, the identity of the indigenous communities has been devalued; Therefore, the present research work proposes to elaborate primers of ancestral knowledge for the strengthening and development of interculturality through the teaching performance in basic general education of the UECIB "Ángel Erminio Silva Olivo". The methodology used is quantitative in nature. For the descriptive scope, a questionnaire was applied to 14 teachers and the results showed a lack of knowledge about ancestral knowledge and the non-implementation of strategies aimed at strengthening interculturality. Based on the exposed problem, the design of intercultural educational primers of ancestral knowledge was proposed for the improvement of the training of teachers, the same ones that describe five components: productive and economic activities, sociocultural experiences, spiritual practices, signs of nature and educational activities. The proposal was assessed by three specialists who rated its structuring criteria, internal logic, importance and ease of implementation as very good and excellent. Finally, the users were receptive to the improvement of knowledge and the results of its application in workshops with teachers, showing the improvement of the level of knowledge to acceptable values.